2010
DOI: 10.1590/s1676-06032010000100013
|View full text |Cite
|
Sign up to set email alerts
|

Biologia reprodutiva de Cercosaura schreibersii (Squamata, Gymnophthalmidae) e Cnemidophorus lacertoides (Squamata, Teiidae) no escudo Sul-Riograndense, Brasil

Abstract: Abstract:Gonads of 124 specimens of Cercosaura schreibersii (Wiegmann, 1834) and 192 specimens of Cnemidophorus lacertoides Duméril & Bibron, 1839 from the Sul-Riograndense Shield, Rio Grande do Sul, Brazil were analyzed. Both species presented seasonal reproduction, with vitellogenic females found at the end of winter and spring, gravid females in spring and summer and recruitment recorded during the months with the higher mean temperatures in the region. Variation of testis volume was not observed in males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 30 publications
2
13
0
13
Order By: Relevance
“…The presence of longer trunks in females may be associated with a fertility advantage conferred by a larger space in the peritoneal cavity for egg development (OLSSON et al 2002, COX et al 2003. A larger trunk length in females is recurrent in many species of Gymnophthalmidae (VITT 1982, VITT & ÁVILA-PIRES 1998, BALESTRIN et al 2010. On the other hand, males presented larger femoral and head lengths than females, a pattern that seems to be common in species of lizards in which the exploration or defense of territories by males, favors success in finding mates (PERRY et al 2004, PETERSON & HUSACK 2006, KALIONTZOPOULOU et al 2010.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of longer trunks in females may be associated with a fertility advantage conferred by a larger space in the peritoneal cavity for egg development (OLSSON et al 2002, COX et al 2003. A larger trunk length in females is recurrent in many species of Gymnophthalmidae (VITT 1982, VITT & ÁVILA-PIRES 1998, BALESTRIN et al 2010. On the other hand, males presented larger femoral and head lengths than females, a pattern that seems to be common in species of lizards in which the exploration or defense of territories by males, favors success in finding mates (PERRY et al 2004, PETERSON & HUSACK 2006, KALIONTZOPOULOU et al 2010.…”
Section: Resultsmentioning
confidence: 99%
“…Vanzosaura rubricauda (Boulenger, 1902) a related species, also shows multiple clutches of two eggs, with a continuous reproduction cycle in the Caatinga (VITT 1982), but a seasonal one in the Chaco (CRUZ 1994). A fixed clutch size of two eggs is a recurring pattern in many species of Gymnophthalmidae (FITCH 1970, TELFORD 1971, SHERBROOKE 1975, VITT 1982, ÁVILA-PIRES 1995, PIANKA & VITT 2003, BALESTRIN et al 2010.…”
mentioning
confidence: 99%
“…ANDERSON & VITT (1990) suggested that head shape is directly related to facilitate mating because males can hold females tightly, besides providing advantages in male-male combat. Males with larger heads (than females) are also found in Cercosaura schreibersii Wiegmann, 1834(BALESTRIN et al 2010 and V. rubricauda (D.C.P.S. Aquino, unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recent increase in the number of studies on the reproduction of Neotropical lizards (e.g., Balestrin et al, 2010;, the knowledge about the reproductive biology of several species is still scarce.…”
Section: Correlação (Mm) Variávelmentioning
confidence: 99%